2022
DOI: 10.1007/s00167-022-07092-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative joint line convergence angle correction is a key factor in optimising accuracy in varus knee correction osteotomy

Abstract: Purpose This study aimed to identify and prevent preoperative factors that can be influenced in preoperative planning to reduce postoperative malcorrections. Methods The method used in this study was a retrospective two-centre analysis of 78 pre and postoperative fully weight-bearing radiographs of patients who underwent valgus osteotomy correction due to symptomatic medial compartment osteoarthritis. A computer software (TraumaCad®) was used to aim for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
(67 reference statements)
0
17
1
Order By: Relevance
“…The overcorrection rate in this study was relatively high compared with that in other studies [11,42], where 42.9% was categorised as overcorrection when the acceptable range was set as 62.5 ± 6.25. Our analysis was conducted only on patients with well-performed bony corrections, and we therefore considered two possibilities.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The overcorrection rate in this study was relatively high compared with that in other studies [11,42], where 42.9% was categorised as overcorrection when the acceptable range was set as 62.5 ± 6.25. Our analysis was conducted only on patients with well-performed bony corrections, and we therefore considered two possibilities.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, we identified a significant correlation between preJLO and ∆JLCA. Consequently, we obtained a model with higher explanatory power in the multiple regression analysis than that used in previous studies [11, 12, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Behrendt et al [39] provided the first evidence that this additional planning step improves the accuracy of varus correction osteotomies and yields reduced postoperative medial proximal tibial angle (MPTA) values.…”
Section: Post‐operative Complicationsmentioning
confidence: 99%
“…Clinical and experimental studies have shown that the JLCA has a normal range between 0° to 2°, which increases in magnitude depending on the severity and stage of osteoarthritis in the knee [1, 2, 10, 37, 39]. A positive value may be caused by an intra‐articular varus deformity with a medial apex [40].…”
Section: Post‐operative Complicationsmentioning
confidence: 99%